Contractive mappings on a premetric space - C. Y. Shen; A. Sound (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study the fixed point property of certain types of contractive mappings defined on a premetric space. The applications of these results to topological vector spaces and to metric spaces are also discussed.